Обґрунтування технологічних параметрів підйомних опалубок під час зведення каркасів багатоповерхових будівель - Тонкачеєв, Г. М.; Кушнарьов, М. В.; Шарапа, С. П. (Ways to Improve Construction Efficiency, 2014)
The paper presents the technological parameters of the lifting of formwork for the construction of multi-storey buildings, results of valuation of time and labor, considered a model of technological processes and dependences for justification of technological decisions are given.